Siedem dokumentów i listów Mikołaja Krzysztofa „Sierotki” i Albrychta Władysława Radziwiłłów z końca XVI i początku XVII wieku dotyczących dziesięcin i innych świadczeń dla kościoła w Czernawczycach i prepozytury Św. Barbary w Brześciu - Gołaszewski, Łukasz (Vilnius University Open Series, 2024)
The present paper contains an editing of seven documents and letters concerning the tithes from Radziwiłł’s estates near Brest for the Catholic parish church in Čarnaŭčycy and St. Barbara provostry in Brest. Senders were two members of the Radziwiłł family: Mikołaj Krzysztof “The Orphan” and Albrycht Władysław and addresses parish priests and land-stewards. This documents are interesting sources of knowledge about relations between them and landlord’s activity in the field of solutions to the disputes about tithes.
Keywords: dziesięciny w Wielkim Księstwie Litewskim; Kościół katolicki w Brześciu; Kościół katolicki w Czernawczycach; Mikołaj Krzysztof Radziwiłł „Sierotka”; Albrycht Władysław Radziwiłł; relacje między magnatami a duchowieństwem katolickim w Rzeczypospolitej polsko-litewskiej